An image cryptography method by highly error-prone DNA storage channel - Zan, Xiangzhen; Chu, Ling; Xie, Ranze; Su, Yanqing; Yao, Xiangyu; Xu, Peng; Liu, Wenbin (Frontiers in Bioengineering and Biotechnology, 2023)
Rapid development in synthetic technologies has boosted DNA as a potential medium for large-scale data storage. Meanwhile, how to implement data security in DNA storage system is still an unsolved problem. In this paper, we propose an image encryption method based on the modulation-based storage architecture. The key idea is to take advantage of the unpredictable modulation signals to encrypt image in highly error-prone DNA storage channel. Numerical results demonstrate that our image encryption method is feasible and effective with excellent security against various attacks (statistical, differential, noise and data loss, etc.). Compared with other methods by DNA molecules hybridization reaction, the proposed method is more reliable and feasible for large-scale applications.